Persepsi Penyakit dan Perawatan Diri dengan Kualitas Hidup Diabetes Mellitus Type 2 - Fitriyanti Nurdin (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the relationship between pain perception and self-care with the quality of life of people with type 2 diabetes. This research method is a quantitative study with a cross-sectional study approach. The results showed that the majority of respondents were female, the age of the majority of respondents was 54.7 years, the majority of respondents' education was SMA-PT, the majority of DM treatment used pills / oral drugs, the majority of DM complications were neuropathy, the majority had long suffered from DM, which was an average of 7, 85 years, there is a significant relationship between pain perception and self-care, there is an important relationship between pain perception and DM quality of life, there is no critical relationship. In conclusion, there is no significant relationship between pain perception and quality of life for type 2 diabetes. There is no meaningful relationship between self-care and quality of life for type 2 diabetes. Keywords: Type 2 Diabetes Mellitus, Quality of Life, Self Care, Perception of Disease